(untitled) (Olhar de Professor, 2019)
Investigations involving the study of infants have been growing in Brazil. It aims to point out some characteristics of the education of the babies, among them. The methodology of observation is used. The central characteristics of this education, with babies, found in the research are: we have a pedagogical practice in which the teachers do not encourage and promote the interaction between the babies and a partial autonomy of these in the planned activities; the interactions through the games still do not reach the proposal of the theory of the exchanges between babies of Mira Stambak and his team - referential of this research. And finally, actions with babies are defined and directed by the adult. Taken together, these findings demand a new “das” look and practices, as well as in relation to the production of knowledge in this theme. In this sense, the present work is characterized as a referential enhancer for other researches, on infants, in Brazilian contexts and of Internship, in Pedagogy courses